Comparison of Effect of Sodium-Glucose Co-Transporter-2 (SGLT-2) Inhibitors with Dipeptidyl Peptidase-4 (DPP-4) Inhibitors on HBA1c Level in Type 2 Diabetes in Pakistani Population - Amir Misbah ul Qamar, Muhammad; Sumreen, Tahira; Khan, Andaleeb; Butt, Kamil Rehman; Ali, Ejaz; Rehman, Ayesha (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the effect of SGLT-2 inhibitors with DPP-4 inhibitors as the add on therapy to Metformin on HBA1c level in type 2 diabetes patients in Pakistani population. Study Design: Quasi-experimental study. Place and Duration of Study: Combined Military Hospital Sialkot, Pakistan from Nov to Apr 2020. Methodology: The study population comprised of 300 type-II diabetes patients with poorly controlled diabetes on Metformin managed at Combined Military Hospital Sialkot, Pakistan. Patients were divided into two groups via lottery method. GroupA received the SGLT-2 inhibitors at standard dose while group-B received the DPP-4 inhibitors at the usual standard does as recommended by the consultant medical specialist. Values of glycosylated hemoglobin were compared three months after the start of study. Results: Mean age of the patients was 44.31 ± 5.841 years. Mean duration of type 2 diabetes mellitus in the study participants was 4.18 ± 6.369 years. HBA1c after three months of treatment in the SGLT-2 inhibitors-group was 7.01 ± 0.14 mmol/L while in the DPP-4 inhibitors-group was 7.89 ± 0.99 mmol/L. Difference between the two groups was statistically significant (pvalue <0.01). The result showed SGLT-2 inhibitors as the better option for add on therapy to Metformin as compared to DPP-4 inhibitors. Conclusion: SGLT-2 inhibitors emerged as better option to lower the HBA1c level as compared to DPP-4 inhibitors as the add on therapy to Metformin as there was statistically significant difference in HBA1c levels after three months of therapy in both the groups.